Architecture: An Introspective Look at the Pedagogical Culture - Corcoran, Erin (University of Waterloo, 2008)
In North America, to become an architect, students must acquire a wide range of knowledge, create designs in studio, and spend some time working in an architecture firm. There are various lessons that they need to learn, and techniques that they develop through their education that combine to give them the necessary skills to write their professional exams. However, the education of an architect is not a process that is simple or straight-forward, and there are a series of other elements that, combined with this basic knowledge, ultimately create contemporary architects. Qualities like individual development, experience, emotional response, personal attitudes, and behaviours are not elements that are going to show up in any architecture school’s brochure, but their effect on the student is just as important as the knowledge that he or she will require to practice. To date, pedagogical inquiry into architecture seems to take two views: either looking at educational techniques and courses; or focusing on the detrimental symptoms of the less-tangible elements mentioned above. This thesis will bridge these two areas by researching the educational process and combining this knowledge with the important but more subjective areas of individual development. Through this study a clearer understanding of the profession will emerge, creating an opportunity for it to improve in the future.
Keywords: architecture; studio culture; education; stress; self-awareness; work life balance; Architecture